Siloxene Nanosheets and Their Hybrid Gel Glasses for Broad-Band Optical Limiting - Lv, Xugui; Li, Nan; Li, Yunfei; Ma, Qingyu; Xie, Zheng; Zhou, Shuyun (Molecules (Basel, Switzerland), 2023)
With the development of laser technology, the research of novel laser protection materials is of great significance. In this work, dispersible siloxene nanosheets (SiNSs) with a thickness of about 1.5 nm are prepared by the top-down topological reaction method. Based on the Z-scan and optical limiting testing under the visible-near IR ranges nanosecond laser, the broad-band nonlinear optical properties of the SiNSs and their hybrid gel glasses are investigated. The results show that the SiNSs have outstanding nonlinear optical properties. Meanwhile, the SiNSs hybrid gel glasses also exhibit high transmittance and excellent optical limiting capabilities. It demonstrates that SiNSs are promising materials for broad-band nonlinear optical limiting and even have potential applications in optoelectronics.